"Forms of Living Death": Mockery, Marronage, and Sovereignty in Percy Shelley and John Gareth Stedman. Issue 2 (October 2016) - Hanson, Lenora
Abstract : This essay presents a novel interpretation of the "trope" of mockery offered at the end of Percy Shelley's "The Sensitive Plant." It argues that mockery undoes the sympathetic relation established between sovereignty and Nature during the romantic period. By comparing Shelley's poem and John Gareth Stedman's Narrative of a Five Years' Expedition, I locate a political and poetic practice that evades such sovereignty by disfiguring the human form. I propose a connection between Shelley's use of mockery and Stedman's account of slave marronage, a process in which escaped slaves were oftentimes described as decaying into or becoming part of a distinctly non-anthropomorphic nature. Both Shelley and Stedman's work asks us to consider how the decay of the human, as a primary reference point for romantic nature, might offer new ways to think the politics of life in romantic literature. Specifically, they help us to think beyond the terms of bare life that Giorgio Agamben has offered in favor of an ecological, anti-colonial life that fuses human and nonhuman bodies together in underground uprisings.